PKG and PKC Are Down-Regulated during Cardiomyocyte Differentiation from Embryonic Stem Cells: Manipulation of These Pathways Enhances Cardiomyocyte Production - Stephen Mobley; Jessica M. Shookhof; Kara Foshay; Michelle Park; G. Ian Gallicano (Stem Cells International)
Understanding signal transduction mechanisms that drive differentiation of adult or embryonic stem cells (ESCs) is imperative if they are to be used to cure disease. While the list of signaling pathways regulating stem cell differentiation is growing, it is far from complete. Indentifying regulatory mechanisms and timecourse commitment to cell lineages is needed for generating pure populations terminally differentiated cell types, and in ESCs, suppression of teratoma formation. To this end, we investigated specific signaling mechanisms involved in cardiomyogenesis, followed by manipulation of these pathways to enhance differentiation of ESCs into cardiomyocytes. Subjecting nascent ESC-derived cardiomyocytes to a proteomics assay, we found that cardiomyogenesis is influenced by up- and down-regulation of a number of kinases, one of which, cGMP-dependent protein kinase (PKG), is markedly down-regulated during differentiation. Delving further, we found that manipulating the PKG pathway using PKG-specific inhibitors produced significantly more cardiomyocytes from ESCs when compared to ESCs left to differentiate without inhibitors. In addition, we found combinatorial effects when culturing ESCs in inhibitors to PKG and PKC isotypes. Consequently, we have generated a novel hypothesis: Down-regulation of PKG and specific PKC pathways are necessary for cardiomyogenesis, and when manipulated, these pathways produce significantly more cardiomyocytes than untreated ESCs.